Testing methods of remanufacture of pre-consumer textiles in scalable environments - Child, Emmeline (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
Despite a growing response by multiple stakeholders to address waste issues in the industry, the consumer appetite for newness and the speed and agility of the mass manufacturing system encourages overconsumption Currently, less than 1% of the material used to produce clothing is recycled into new clothing. As Walter Stahel notes, wasted material is also wasted money, meaning that increasingly industry stakeholders are looking to exploit the potential economic benefit of ‘remanufacture’ or ‘upcycling’. While many micro-businesses are utilising upcycling on a small scale, the impact on the overall resource wastage is minimal. This paper explores how working in a factory environment can give greater insight into the challenges of working with remanufacture for scale. It will support a greater understanding of the barriers that are impeding the widespread adoption of working with Whole Product (WP) fallout on a production line, while helping to identify the frameworks needed to support methods of WP Remanufacture (WPRem) within the linear commercial environment.